Anglicisms in the linguistic and didactic perspective - Kowalonek-Janczarek, Monika (Glottodidactica, 2014)
The aim of this paper is to investigate the problem of defining the term Anglicism in academic papers dealing with this problem. The focus is on different linguistic approaches to Anglicisms discussed from the sociolinguistic, diachronic and synchronic perspectives. The complexity of the subject together with the multiplicity of the presented approaches have consequences for teaching German as a FL. These problems are presented in the second part of the paper.